Sujeitos da Educação de Jovens e Adultos e as tecnologias: o cotidiano pedagógico da EJA durante a pandemia em uma escola estadual na Região Norte de Belo Horizonte - MG - Ana Karina Ladeira Gomes (2024)
The research presented here aimed to explore the impact of the covid-19 pandemic on education, with a specific focus on Youth and Adult Education (EJA) and the use of Digital Information and Communication Technologies (TDICs). The central object of the research was to analyze how the pandemic has affected the educational process of EJA students and how TDICs have been integrated into pedagogical practices to mitigate these effects. The methodology adopted was qualitative in nature, involving fieldwork and detailed analysis of a specific school, called Metropolitan School C. Data collection included semi-structured interviews with EJA students and document analysis. The results of the research indicate that, during the pandemic, there was a significant adaptation in pedagogical practices, with teachers developing new remote teaching strategies. TDICs have emerged as essential tools, but they have also revealed inequalities of access and technical challenges. The research revealed that, despite efforts to keep education active, many EJA students faced significant difficulties, including withdrawal from school due to financial and technological issues. Finally, it should be noted that the researcher's experience and the learning acquired during the scientific investigation provided valuable insights into resilience and innovation in education in times of crisis. This research can contribute to the improvement of pedagogical practices with regard to the use of TDICs, especially in the context of EJA, through the product generated from this investigation consisting of a booklet with basic notions for learning Word and Power Point software and for developing internet searches.